Kultur Pemberian Ranking Kelas di Pesantren dan Relevasinya dengan Spirit Merdeka Belajar - Malili, Rusli; Palangkey, Rahmi Dewanti; Rijal, Tabhan Syamsu; Tazali, Imam (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2022)
The study of independent learning is very interesting because it involves the novelty of educational civilization, but what is interesting is when Islamic boarding schools have already applied the value of independent learning in the aspect of providing value for learning outcomes. This research was conducted to find answers to why Pesantren Nurulhuda chose not to give rankings as a reward for learning outcomes. The results of this study indicate that they want to view and respect all their students fairly and proportionally. Not only based on IQ intelligence, the culture of the Nurulhuda Islamic boarding school by not publishing the rankings in our class is drawn to the spirit of free learning, which is called diverse assessment. So this pesantren is relevant. The wisdom of the Islamic boarding school in this case Nurulhud a by giving rewards is not against any rules because now School-Based Management (SBM) has been implemented.